Digital Literacy Skills of Tutors: A Case Study at Universitas Terbuka - Iqbal Miftakhul Mujtahid; Radeswandri Radeswandri (Action Research Journal Indonesia (ARJI), 2025)
Digital literacy is a skill to understand and utilize information from various digital sources. Digital literacy skill is useful for dealing with information explosions. In fact, internet users nowadays keep increasing. The problem is that technological advances lead to excessive use of information technology, leading to undesirable cases. Therefore, this study aimed to map digital literacy of tutors at Universitas Terbuka. This research used a quantitative approach with a case study method. Informants used as research samples were 127 tutors from Universitas Terbuka. Data on digital literacy skills of tutors were collected through online questionnaires using Google Form, then analyzed descriptively and inferentially using SPSS Program version 23.00 for Windows. Results showed that instrument used was a digital literacy ability questionnaire consisting of eight constructs with an average Croanbach’s alpha value of 0.859 with high criteria. Importantly, results also showed that there was a significant relationship between basic, scientific, economic, information, technological, visual, multicultural, and global awareness. Based on value of correlation coefficient, economic ability, visual intelligence, and technological intelligence had the highest values (0.613, 0.554 and 0.513), showing that the three constructs were better constructs in increasing digital literacy of tutors. In other words, these results provide empirical evidence that tutors' digital literacy is not only influenced by the technical ability to use digital devices, but also by the ability to understand aspects of the digital economy, information visualization, and the application of technology in the context of learning. This certainly has an impact on the quality of teaching and the readiness of tutors in facing educational transformation in the digital era.